Pengaruh Sikap Keuangan Dan Pengetahuan Keuangan Terhadap Perilaku Keuangan Pada Ibu Rumah Tangga Di Kecamatan Tirawuta Kabupaten Kolaka Timur - Astaginy, Niar; Zulbay, Agus; Cornelius, Jean Angrid (LPPM Universitas BSI, 2023)
This study aims to determine: (1) The effect of financial attitudes on financial behavior of housewives in Tirawuta District, East Kolaka Regency. (2) The Effect of Financial Knowledge on Financial Behavior of Housewives in Tirawuta District, East Kolaka Regency. This study uses an approach with quantitative methods. The population of this research is housewives. While the sample of this study amounted to 100 people. Based on the research results it is known that the financial attitude variable has a positive and significant value on financial behavior as indicated by a T-statistic value of 5,765 with a P value of 0,000. the financial knowledge variable has a positive and significant effect on financial behavior which is shown by a T-Statistic value of 4,574 with a P-Value of 0,000. The conclusion of this study is that the ability and understanding of financial attitudes and knowledge in influencing financial behavior are in the strong category, so it is hoped that the results of this study can become a reference or reference for developing further research related to factors that influence financial behavior so that better results are obtained.Keyword: Financial Attitude, Financial Knowledge, Financial Behavior